Dependancy graph scheduling on arbitrary multiprocessor systems using the colevel ascending method - 501782 Mohd. Norsyarizad Razali; Shaharuddin Salleh, Supervisor; Fakulti Sains (2004)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2004